Prospects for integrating food and feed production in Welayta Sodo, Ethiopia - Tolera, Adugna; Said, A.N. (International Livestock Centre for Africa, 1992)
A diagnostic survey was carried out in 1988 to assess feed resource and animal production situation in Welayta Sodo. Information was collected by interviewing 102 heads of households. Supplementary information was also collected from the Ministry of Agriculture. Discusses type and nutritional quality of available feed resources; estimated quality of feed resources available in Welayta District including crop residues; availability of feed DM relative to livestock population of the District; livestock productivity, major constraints to livestock production, and prospects for integrating food and feed production with ref. to traditional complementarity of food & feeds; stratification of livestock production; and temporal interaction between forage supply and demand.